Analisis Kinerja Saluran Drainase Menggunakan Perangkat Lunak HEC-RAS 6.0: Studi Kasus Jl. Letjend Suprapto, Batam - Tria Resinta; Ade Jaya Saputra; Amanatullah Savitri (LPPM Universitas Abdurrab, 2025)
Poor drainage conditions, such as clogged and damaged channels, cause flooding problems. The research was conducted on Jalan Letjend Suprapto, Batam City, which has rainfall data from 2014 to 2023. The results of the analysis showed that the existing drainage system could not accommodate high rainfall that could cause flooding. The peak discharge of 0.2733 m3/s and the rain intensity of 127.24 mm/hour were obtained using hydrological and hydraulic analysis methods. Simulations using HEC-RAS 6.0 revealed that the current capacity of drainage channels is inadequate, resulting in water overflow. Therefore, this study suggests the need to normalize channels or create drainage channels with larger dimensions to reduce the risk of flooding in the future.